Analisa Kerusakan Dan Perawatan Pada Travel Motor Unit Excavator 320D Caterpillar - Mangkona Mangkona; Abdul Halik; Hidayat Hidayat; Abdul Halim; Yudi Nurhikmat (Politeknik Negeri Samarinda, 2022)
Motor travel serves as a steering and braking system, driving the unit forward, backwards and to the side with the help of a hydraulic system. The hydraulic system plays a very important role in the operation of the machine. The fundamentals of hydraulic and advanced hydraulics, and applied failure analysis support the knowledge of engineering students. The method used is to carry out the disassembly and analysis of the travel motorbike with the aim of identifying the damage that occurred. Visual analysis of traction motors, head/valves, brake valves, brake pistons. These components can be reused after cleaning the components. There is also such a type of damage to traction motor components as wear and tear. This wear is found in retaining shoes, port plates, cylinders, pistons, camshafts, and shafts. . After visual analysis, the next step is measurement. The measured part is a spring. The results of the analysis proved that the measurement of this spring does not correspond to the information provided in the literature.